RESEARCHING INDONESIAN STUDENTS’ ATTITUDE TOWARDS FOREIGN LANGUAGE - Ardi Marwan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Foreign language attitude plays a significant role in enhancing ones’ motivation to learn a particular foreign language. This study aims to obtain an understanding  of Indonesian students’ attitude towards Japanese language.  The  data  were  collected  from  160  students  learning  Japanese. Foreign language attitude questionnaire (FLAQ) originally developed by Pierson et al. (1980) was used in this study. Further, attitude factors identified by Pennington and Yu (1994) following the result of FLAQ factor analysis was also incorporated in the current research. It is evident in this study that the majority of students showed positive attitude towards Japanese language. That is, they showed no negative orientation towards this foreign language and culture. The study also observed no significant differences in attitude towards Japanese language between male and female students (p>.05). Both males and females responded positively on their Japanese language learning and use.